PsycEXTRA Dataset 2011
DOI: 10.1037/e505232012-005
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Association: Inclusion of Other in the Self and Self-Disclosure

Abstract: The current study examined the relationship between inclusion of other in the self (a theoretically distinct conceptualization of relationship closeness) and self-disclosure. These constructs were also examined in association with relationship outcomes of satisfaction and commitment. Analysis of the data indicated that inclusion of other in the self and self-disclosure in a relationship were each significantly positively correlated with both relationship satisfaction and commitment. However, there was no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Being rooted in one's specific relationship, couple identity is a relationship asset, strenuously defended in the presence of perceived threat (Martz et al, ; Nehrlich, Gebauer, & Sedikides, ; Rusbult, Van Lange, Wildschut, Yovetich, & Verette, ). It is appropriate that couple identity is considered a relationship asset: It predicts relationship satisfaction (Acitelli, ; Acitelli & Young, ; Agnew, Van Lange, Rusbult, & Langston, ; Aron & Aron, ; Lewandowski et al, ; Parise et al, ; Wiedler & Clark, ), relationship commitment (Lewandowski et al, ), and relationship stability (Aron, Aron, & Smollan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Being rooted in one's specific relationship, couple identity is a relationship asset, strenuously defended in the presence of perceived threat (Martz et al, ; Nehrlich, Gebauer, & Sedikides, ; Rusbult, Van Lange, Wildschut, Yovetich, & Verette, ). It is appropriate that couple identity is considered a relationship asset: It predicts relationship satisfaction (Acitelli, ; Acitelli & Young, ; Agnew, Van Lange, Rusbult, & Langston, ; Aron & Aron, ; Lewandowski et al, ; Parise et al, ; Wiedler & Clark, ), relationship commitment (Lewandowski et al, ), and relationship stability (Aron, Aron, & Smollan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intimacy and closeness are considered the key benefits in a relationship (Fruzzetti and Iverson 2004). Closeness correlates positively with relationship quality and satisfaction (Agnew et al 2004;Crespo et al 2008;Cropley and Reid 2008;Weidler and Clark 2011). A meta-analysis that included 19 studies (Le et al 2010) showed that a higher closeness score is associated with a lower probability of separation, with an effect size of Cohen's d = − .70.…”
mentioning
confidence: 99%
“…Couple identity is linked with important dimensions of couple relationship functioning such as relationship quality (Agnew, Van Lange, Rusbult, & Langston, 1998; E. N. Aron & Aron, 1996; Lewandowski, Nardone, & Raines, 2010; Parise, Manzi, Donato, & Iafrate, 2017; Weidler & Clark, 2011), relationship stability (A. Aron, Aron, & Smollan, 1992), and commitment (Agnew et al, 1998; Lewandowski et al, 2010).…”
mentioning
confidence: 99%